Perceptions of responsible human resources management and credibility of the Public Administration: the mediating role of service quality and satisfaction - Vázquez Burguete, José Luis; Lanero Carrizo, Ana; García Miguélez, María Purificación (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
This study extends previous literature on corporate social responsibility (CSR) in private firms and consumer behavior to set a model of citizen perceptions of responsible human resources management (HRM) in the public administration. Particularly, the main goal of the paper is to analyse the effect of perceived internal responsibility on credibility, by considering the mediating role of quality of service and satisfaction. A survey study was conducted with a total sample of 660 Spanish citizens. Structural equations modelling with PLS (Partial Least Squares) was used to test the overall fit of the model. In sum, results provided support for all the relations hypothesised. Findings and their implications are described.